Maternity care professionals’ preparedness for and experiences of screening and responding to disclosures of domestic violence in the peripartum period: A protocol for a qualitative evidence synthesis - Laura O’Shea; Melissa Corbally; Deirdre Daly (PLoS ONE, 2025)
Background Maternity care professionals, such as midwives, public health nurses, doctors, and social workers, are in the unique position of having regular contact with women in the peripartum period. They are well-placed to recognise and respond to disclosures of domestic violence, however many lack confidence and feel unprepared for this in practice. While there are screening tools used for enquiry about domestic violence in pregnancy, there are variations in the tools used, the frequency and timing of enquiry, and the response/referral pathways across professions. Research exists on the role of health care professionals such as midwives, doctors, and nurses with regards to domestic violence, however little is understood about the collective and shared experience of maternity care professionals who screen for and respond to domestic violence in the peripartum period. Methods A qualitative evidence synthesis of maternity care professionals’ preparedness for and experiences of screening and responding to disclosures of domestic violence in the peripartum period will be conducted. Qualitative studies of any design, and mixed method and other design studies where qualitative data can be extracted will be considered for inclusion. A systematic search of the following electronic bibliographic databases will be conducted: ASSIA, CINAHL, EMBASE, Maternity and Infant Care, MEDLINE, APA PsycINFO and SocINDEX. The Critical Skills Appraisal Programme (CASP) qualitative studies tool will be used to assess methodological quality of included studies. Data synthesis will involve three sequential stages, coding, development of descriptive themes and generation of analytical themes. Confidence in findings will be assessed using the Grading of Recommendations Assessment, Development and Evaluation-Confidence in the Evidence from Reviews of Qualitative research (GRADE-CERQual) tool. Discussion This QES will provide a deeper understanding of maternity care professionals’ preparedness for and experiences of screening and responding to domestic violence disclosures in the peripartum period. The findings will, potentially, identify what aspects of education and preparedness work well and what might be improved.